Détection précoce des troubles psychiques en milieu scolaire : le dispositif Fil Harmonie - Oppetit, A.; Brébant, C.; Monchablon, D.; Bourgin, J.; Gaillard, R.; Olié, J. -P.; Krebs, M. -O.; Morvan, Y. (L'Encéphale, 2018)
Résumé Objectif L’objectif de cette étude est de décrire le fonctionnement du dispositif Fil Harmonie, ligne téléphonique réservée aux professionnels de l’Académie de Paris faisant face à une situation d’un élève en souffrance psychologique ou psychiatrique. Méthodes Il s’agit d’une étude descriptive observationnelle réalisée entre le 18 septembre 2013 et le 12 mai 2014. Les informations transmises lors des 68 appels téléphoniques ont été recueillies, formalisées puis analysées. Nous avons utilisé une méthodologie mixte, associant des analyses de données quantitatives et de données textuelles. Résultats La profession de l’appelant était dans plus de 70 % des cas celle d’infirmière scolaire. L’âge moyen des élèves concernés était de 17,3 ans. Les deux classes les plus représentées étaient la seconde et la classe préparatoire (19,7 % dans les deux cas). Plus de la moitié des jeunes étaient déclarés comme n’ayant jamais eu de prise en charge psychologique antérieure (52,5 %). Les jeunes étaient décrits majoritairement comme isolés socialement (67,2 %), tristes ou anhédoniques (48,2 %). Plus d’un quart (26,7 %) avait déjà redoublé au moins une fois et la majorité (55,9 %) faisait preuve d’absentéisme. L’analyse qualitative a mis en évidence la complexité de la collaboration entre la famille de l’élève et l’établissement scolaire. Conclusion Fil Harmonie propose une nouvelle modalité pour favoriser le dépistage des difficultés psychiques chez les jeunes en milieu scolaire. Ce dispositif aide à la résolution de problème et si nécessaire l’orientation vers des professionnels de santé adéquats grâce à l’intervention d’un professionnel relais. Cette étude de terrain pointe la nécessaire articulation entre professionnels de l’Éducation, professionnels de santé et entourage proche. Objective Most psychiatric disorders arise during adolescence, a period of life during which school takes an important place. School in France has an official mission of health education and prevention, and early detection of mental disorders is part of these goals. The aim of this study is to describe an innovative service operating in Paris that helps educational staff to deal with students having psychological or psychiatric symptoms. The Fil Harmonie program was launched in 2011. It consists of a telephone line available to all educational staff working for high schools in Paris. Methods When in need of assistance, a member of the educational staff can call the dedicated hotline and expose the situation of their student to a trained psychologist. Over the course of the study, data concerning these phone calls were collected such as: socio-demographic characteristics of the student, the reason behind the call, the caller's professional role within the school, and care pathway information. All data collected during the phone calls were anonymized and computerized. We performed an observational descriptive study based on this data by using mixed methods: we integrated quantitative analysis and qualitative research in order to provide a better understanding of the Fil Harmonie program. Results Between 18 September 2013 and 12 May 2014, the Fil Harmonie program handled 68 calls from educational staff. Students concerned by the calls were aged between 11 and 22 and the average age was 17.3 years. Over half (52.5%) of the pupils concerned had never seen a mental health professional before the call. In more than 70% of cases, the caller was a school nurse while other professionals such as teachers or headmasters represented only a minority of the callers. Approximately two thirds (67.2%) of students were described by the caller as socially isolated and 48.2% were described as sad or anhedonic. One out of four (26.7%) had repeated a school year at least once, and 55.9% of young people for whom a member of staff contacted Fil Harmonie had been missing class. In 56.7% of cases, there had been no contact with the student's family about the psychological situation. The qualitative analysis particularly highlighted the complexity of the collaboration between the family and the educational staff. Conclusion Schooling is an important opportunity to seize in mental health regarding early detection and access to care. By fostering collaboration between educational professionals and mental health services, Fil Harmonie meets a public health objective of prevention and should contribute to the reduction of care delays thus leading to better treatment outcome. Our study shows that such programs are feasible and answer a real need in our current health care system.
Keywords: Access to care; Accès aux soins; Détection précoce des troubles psychiatriques; Early detection; Educational health; Mixed methods; Méthodes mixtes; Prevention; Prévention; Santé scolaire